Development of a method for the search of solutions in the sphere of national security using bio-inspired algorithms - Koval, Volodymyr; Shyshatskyi, Andrii; Ransevych, Ruslan; Gura, Viktoriya; Nalapko, Oleksii; Shypilova, Larysa; Protas, Nadiia; Volkov, Oleksandr; Stanovskyi, Oleksandr; Chaikovska, Olena (Eastern-European journal of enterprise technologies, 2023)
The object of research are decision support systems. The subject of research is the decision-making process in management problems using bio-inspired algorithms. A method for the search of solutions in the field of national security using bio-inspired algorithms is proposed. The proposed method is based on a combination of an artificial bat algorithm and evolving artificial neural networks. The method has the following sequence of actions: ‒ input of initial data; ‒ processing of initial data taking into account the degree of uncertainty; ‒ numbering of bat agents (BA); ‒ placement of bat agents taking into account the degree of uncertainty about the state of the analysis object in the search space; ‒ setting the initial BA speed and the echolocation frequency of each BA; ‒ starting a local search; ‒ launching a global search; ‒ training knowledge bases of bat agents. The originality of the proposed method consists in the arrangement of bat agents taking into account the uncertainty of initial data, improved global and local search procedures taking into account the noise degree of data about the state of the analysis object. Another feature of the proposed method is the use of an improved procedure for training bat agents. The training procedure consists in learning the synaptic weights of an artificial neural network, the type and parameters of the membership function, the architecture of individual elements and the architecture of the artificial neural network as a whole. The method makes it possible to increase the efficiency of data processing at the level of 13–21 % due to the use of additional improved procedures. The proposed method should be used to solve the problems of evaluating complex and dynamic processes in the interests of solving national security problems Об’єктом дослідження є системи підтримки прийняття рішень. Предметом дослідження є процес прийняття рішення в задачах управління за допомогою біоінспірованих алгоритмів. Запропоновано методику пошуку рішень в сфері національної безпеки з використанням біоінспірованих алгоритмів. Запропонована методика заснована на поєднанні штучного алгоритму кажанів та штучних нейронних мереж, що еволюціонують. Методика має наступну послідовність дій: ‒ введення вихідних даних; ‒ оброблення вихідних даних з урахуванням ступеню невизначеності; ‒ нумерація агентів-кажанів (АК); ‒ розставлення агентів-кажанів з урахування ступеню невизначеності про стан об’єкту аналізу у просторі пошуку; ‒ задання початкової швидкості АК та частоти ехолокації кожного АК; ‒ запуск локального пошуку; ‒ запуск глобального пошуку; ‒ навчання баз знань агентів-кажанів. Оригінальність запропонованої методики полягає у розставленні агентів-кажанів з урахуванням невизначеності вихідних даних, удосконаленими процедурами глобального та локального опушку з урахуванням ступеню зашумленості даних про стан об’єкту аналізу. Також особливістю запропонованої методики полягає в використанні удосконаленої процедури навчання агентів-кажанів. Процедура навчання полягає в тому, що відбувається навчання синаптичних ваг штучної нейронної мережі, типу та параметрів функції належності, а також архітектури окремих елементів і архітектури штучної нейронної мережі в цілому. Використання методики дозволяє досягти підвищення оперативності обробки даних на рівні 13–21 % за рахунок використання додаткових удосконалених процедур. Запропоновану методику доцільно використовувати для вирішення задач оцінки складних та динамічних процесів в інтересах вирішення завдань національної безпеки